2010
DOI: 10.1021/jp911953z
|View full text |Cite
|
Sign up to set email alerts
|

Spin Controlling in Narrow Zigzag Silicon Carbon Nanoribbons by Carrier Doping

Abstract: By means of first-principles calculations we predict that it is possible to manipulate the magnetization and magnetization direction in narrow zigzag silicon carbon nanoribbons (ZSiC NRs) by carrier (hole and electron) doping. Without doping, the ground state of the ZSiC NRs wider than 0.6 nm is ferrimagnetic with local magnetic moments at the edge atoms C and Si that are passivated by the hydrogen atoms, and their orientations are parallel at each zigzag edge and are antiparallel between the two edges. Conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
53
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 64 publications
1
53
0
Order By: Relevance
“…48 It was also found that holes and electrons injected by removing or adding electrons from the ZSiC NRs resulted in the magnetization and change of the magnetization direction of the ZSiC NRs. 49 Here, we present new findings on the N-ZSiC NR by hole and electron doping. We investigated the width (N) dependence on the magnetization of N-ZSiC NR with electron and hole doping.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…48 It was also found that holes and electrons injected by removing or adding electrons from the ZSiC NRs resulted in the magnetization and change of the magnetization direction of the ZSiC NRs. 49 Here, we present new findings on the N-ZSiC NR by hole and electron doping. We investigated the width (N) dependence on the magnetization of N-ZSiC NR with electron and hole doping.…”
Section: Introductionmentioning
confidence: 86%
“…46,47 We recently reported that the zigzag silicon carbon nanoribbons (ZSiC NRs) can be utilized for manipulating the magnetization by applying an electric field 48 and carrier (hole and electron) doping. 49 It was found that the ZSiC NRs showed the magnetization by a transverse electric field as well as the conversion of spin polarization. 48 It was also found that holes and electrons injected by removing or adding electrons from the ZSiC NRs resulted in the magnetization and change of the magnetization direction of the ZSiC NRs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the ZSiC NRs wider than 0.6 nm and narrower than 1.7 nm, the ground state is a ferrimagnetic state with two different direct band gaps for the spin-up and the spin-down channels, and thus it is semiconducting instead of half-metallic. Moreover, they reported that the ZSiC NRs can be utilized for manipulating the magnetization by applying an electric field [25], as well as by carrier (hole and electron) doping [26]. Recently, Zheng et al [27] studied the band-gap modulations of SiC NRs by transverse electric fields.…”
mentioning
confidence: 99%